PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS SPARKOL VIDEOSCRIBE TERHADAP PESERTA DIDIK KELAS XI MAN 1 PASAMAN BARAT - Monhartini Monhartini; Abdul Razak; Irdawati Irdawati; Dwi Hilda Putri (Postgraduate, University of Mataram, 2023)
This research aims to produce learning videos on circulation system material and the digestive system in humans that are valid, practical, and effective. The type of research used is development research using the Plomp development model. The development stage of this model starts from the initial investigation stage, the development or prototyping stage, and the assessment stage. The instruments used in this development research were teacher interview guideline instrument sheets, student response questionnaire sheets, self-evaluation sheets, and learning video validation sheets by experts, as well as learning video practicality assessment sheets filled out by teachers and students. The results of developing learning videos obtained very valid products with a value of 88.71%. The practicality of teachers and students is very practical with scores of 93.3 and 89.75%. The effectiveness test of this learning video is effective because based on the T-test conducted, there is a significant difference between the experimental class and the control class, namely the significance of 0.026, which means that the use of learning videos has an effect on improving student learning outcomes.